Diverse responses of common vole (Microtus arvalis) populations to Late Glacial and Early Holocene climate changes – Evidence from ancient DNA. (1st April 2020) - Baca, Mateusz; Popović, Danijela; Baca, Katarzyna; Lemanik, Anna; Doan, Karolina; Horáček, Ivan; López-García, Juan Manuel; Bañuls-Cardona, Sandra; Pazonyi, Piroska; Desclaux, Emmanuel; Crégut-Bonnoure, Evelyne; Berto, Claudio; et al.
Abstract : The harsh climatic conditions during the Last Glacial Maximum (LGM) period have been considered the cause of local extinctions and major faunal reorganizations that took place at the end of the Pleistocene. Recent studies have shown, however, that in addition many of these ecological events were associated with abrupt climate changes during the so-called Late Glacial and the Pleistocene/Holocene transition. Here we used ancient DNA to investigate the impact of those changes on European populations of temperate vole species ( Microtus arvalis ). The genetic diversity of modern populations and the fossil record suggests that the species may have survived cold episodes, like LGM, not only in the traditional Mediterranean glacial refugia but also at higher latitudes in cryptic northern refugia located in Central France, the northern Alps as well as the Carpathians. However, the details of the post-glacial recolonization and the impact of the Late Glacial and Early Holocene climate changes on the evolutionary history of the common vole remains unclear. To address this issue, we analysed mtDNA cytochrome b sequences from more than one hundred common vole specimens from 36 paleontological and archaeological sites scattered across Europe. Our data suggest that populations from the European mid- and high latitudes suffered a local population extinction and contraction as a result of Late Glacial and Early Holocene climate and environmental changes. The recolonization of earlier abandoned areas took place in the Mid- to Late Holocene. In contrast, at low latitudes, in Northern Spain there was a continuity of common vole populations. This indicates different responses of common vole populations to climate and environmental changes across Europe and corroborates the hypothesis that abrupt changes, like those associated with Younger Dryas and the Pleistocene/Holocene transition, had a significant impact on populations at the mid- and high latitudes of Europe. Highlights: Post-glacial history of the European common vole reconstructed using ancient DNA. Population turnovers at mid- and high latitudes at Pleistocene/Holocene transition. Continuity of common vole populations at low latitudes.